Factors associated with insomnia and suicidal thoughts among outpatients, healthcare workers, and the general population in Taiwan during COVID-19 pandemic: a cross-sectional study - Yi-Hsuan Lin; Jung-Sheng Chen; Po-Ching Huang; Mei-Yun Lu; Carol Strong; Chung-Ying Lin; Mark D. Griffiths; Nai-Ying Ko (BMC, 2022)
Abstract Background Insomnia and suicidal thoughts are two of the negative impacts that have been caused by the COVID-19 pandemic. Identifying the factors that contribute to these psychological problems may help develop strategies to sustain the mental health of the public. The present study examined the psychosocial impacts caused by the COVID-19 pandemic among different populations in Taiwan, and investigated the relationships between these psychosocial variables, insomnia, and suicidal thoughts. Methods Between September 2020 and May 2021, online questionnaires including psychometrically validated scales were distributed to a convenience sample of outpatients (n = 205), healthcare workers (HCWs) (n = 500), and individuals in the general population (n = 1200) in Taiwan to collect data regarding their insomnia severity, suicidal thoughts, fear of COVID-19, trust of information, and resilience. Multivariate logistic regression methods were used to identify variables associated with suicidal thoughts and insomnia. Results Greater fear of COVID-19 was significantly associated with suicidal thoughts: odds ratios (ORs) with 95% confidence interval (CI) = 1.155 (1.002-1.330) for outpatients; 1.127 (1.035-1.228) for HCWs; and 1.100 (1.130-1.222) for those in the general population. Higher resilience was significantly associated with lower insomnia: OR (95% CI) = 0.819 (0.725-0.926) for outpatients; 0.803 (0.728-0.887), for HCWs; 0.829 (0.785-0.875), and for those in the general population. In addition, there was a statistically significant association between insomnia diagnosis and greater fear of COVID-19 among HCWs (OR [95% CI] = 1.102 [1.062-1.144]) and those in the general population (OR [95% CI] = 1.079 [1.053-1.106]). Among outpatients, there was a statistically significant association between suicidal thoughts and lower trust of information (OR [95% CI] = 0.794 [0.646-0.976]), while among those in the general population there was a statistically significant association between suicidal thoughts and higher insomnia severity (OR [95% CI] = 1.175 [1.13-1.222]). A statistically significant association was also found between insomnia diagnosis and higher suicidal thoughts among those in the general population (OR [95% CI] = 3.455 [2.338-5.106]). Conclusions Trust of information, fear, and resilience were important factors for suppressing suicidal thoughts and insomnia among the three study populations. Health policies that monitor psychological status and build resiliency of the public are recommended to help develop tailored strategies for different populations affected by the COVID-19 pandemic.